1865 Del. Laws 930 - (:unkn) unknown (My University, 1865)
An Act to Prevent the Loading of Gunpowder Within Certain Distances of Railroads, chap. 554, § 1: Prohibited loading gun powder into any rail cars within one hundred yards of the track used for carrying passengers.Violators fined one thousand dollars and imprisoned six months.
Keywords: GUNPOWDER - TRANSPORTATION